Burkitt Lymphoma: Pathogenesis and Immune Evasion. (7th September 2010) - God, Jason M.; Haque, Azizul
Abstract : B-cell lymphomas arise at distinct stages of cellular development and maturation, potentially influencing antigen (Ag) presentation and T-cell recognition. Burkitt lymphoma (BL) is a highly malignant B-cell tumor associated with Epstein-Barr Virus (EBV) infection. Although BL can be effectively treated in adults and children, leading to high survival rates, its ability to mask itself from the immune system makes BL an intriguing disease to study. In this paper, we will provide an overview of BL and its association with EBV and the c-myc oncogene. The contributions of EBV and c-myc to B-cell transformation, proliferation, or attenuation of cellular network and immune recognition or evasion will be summarized. We will also discuss the various pathways by which BL escapes immune detection by inhibiting both HLA class I- and II-mediated Ag presentation to T cells. Finally, we will provide an overview of recent developments suggesting the existence of BL-associated inhibitory molecules that may block HLA class II-mediated Ag presentation to CD4+ T cells, facilitating immune escape of BL.